Erasmus experience at Universidade Portucalense: a case study - Gandra, Paulo Rúben Santos (2021)
An analysis of the impact of student mobility under the Erasmus+ program in a regional private university in Porto, Portugal, is presented. This case study is related to the impact of the Erasmus+ Programme, in its phase between 2014 and 2021, and its student mobility strand, at the Universidade Portucalense Infante D. Henrique. The methodology of this case study translates into a documentary and doctrinal analysis, focusing on European Unionrelated documentation. The structure of this article reveals to the reader a brief overview of the history and evolution of the Erasmus+ Programme, clarifies the issue of European identity debated among several authors, as well as the impact of the program itself in the current academic context, and ends with a case study regarding the effects of student mobility in this private university based in Porto, Portugal.